A beginner’s guide to molecular docking (Sciences of Phytochemistry, 2022)
In this opinion, the basics of molecular docking (MD) such as binding affinity, binding pose, and ligand interactions with common docking-related terminologies (Apo protein, positive control, native ligand, co-crystal inhibitors) are discussed. We have provided different figures to aid in the graphical interpretation of the discussed literature. Following this, a few advantages (simplicity, fast, applicability) and disadvantages of MD are highlighted. This opinion will benefit bachelor and master students (or anyone) that are interested in learning the technique of MD. We encourage the sensible use of the MD technique and strict analysis to avoid interpretation errors in the results. The binding affinity, binding pose, and ligand interactions should be collectively considered during the result analysis. For every study, we strongly recommend a strict validation of the docking protocols.